Evaluating the Nao Robot in the Role of Personal Assistant: The Effect of Gender in Robot Performance Evaluation - Vega Vega, Adrián (2019)
By using techniques such as the Wizard of Oz (WoZ) and video capture, this paper evaluated the performance of the Nao Robot in the role of a personal assistant, which was valuated alongside the impact of the assigned gender (male/female) in the perceived performance of the robot assistant. Within a sample size of 39 computer sciences students, this study assessed criteria such as: perceived enjoyment, intention to use, perceived sociability, trust, intelligence, animacy, anthropomorphism, and sympathy, utilizing testing tools such as Unified Theory of Acceptance and Use of Technology (UTAUT) and Godspeed Questionnaire (GSQ). These methods identified a significant effect of the gender assigned to the robot in variables such as intelligence and sympathy.